Gestión de la banca pública: una alternativa para los sectores de la economía no bancarizados (2013)
This article aims to analyze the management of public banks as an alternative for unbanked economy sectors; the methodology used is descriptive documentary bibliographic design. One of the main functions of the national government of the Bolivarian Republic of Venezuela through public banks is to give impetus and insert in the productive sector to all entrepreneurs and businesses who wish to contribute to the economic development of the country. Thus, public banks organizational efforts in projecting their products and / or financial services, through the media and tools, especially those people who do not have regular access to traditional banking services, namely serving enterprising people that is embedded in the so-called informal economy. That is, to have a transparent and efficient official bank that would promote saving, channel credit to growth projects, aimed at meeting with Venezuelan state policies and not special interests.